A composite lithium ion adsorbent based on montmorillonite and preparation method thereof
By using natural montmorillonite and SiO2 activation technology, an efficient montmorillonite-based composite lithium ion adsorbent was prepared, which solved the problems of high cost and small adsorption of existing aluminum-based adsorbents, and achieved efficient separation of lithium ions in brine and the effective utilization of montmorillonite resources.
Patent Information
- Application Number
- CN202410608516.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-16
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-05-16
AI Technical Summary
The existing aluminum-based lithium-ion adsorbent has high synthesis cost and a small amount of lithium-ion adsorption, making it difficult to effectively separate lithium ions in brine.
Using natural montmorillonite as raw material, through SiO2 activation, chemical grafting and co-precipitation technology, montmorillonite-based organic-inorganic composite lithium ion adsorbent was prepared, and LiCl·2Al(OH)3·nH2O and sulfonic acid groups were introduced to form Highly efficient lithium ion adsorbent.
It reduces the synthesis cost, improves the adsorption capacity of lithium ions, realizes effective separation of lithium ions in brine, and effectively utilizes montmorillonite resources.
Smart Images

Figure CN118403607B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion enrichment and extraction in lithium-containing energy minerals, and in particular to an adsorption material for lithium ions in brine, specifically a montmorillonite-based composite lithium ion adsorbent and a preparation method thereof. Background Art
[0002] With the rapid development of my country's new energy industry, the demand for lithium and lithium salts has increased year by year. The research on brine lithium extraction related technologies has become a hot spot and focus of lithium resource development.
[0003] At present, the methods of extracting lithium from brine and adsorption have attracted much attention due to their advantages such as simple process flow, easy implementation and renewable adsorbents. At present, the adsorbent materials that have been studied a lot and have achieved certain lithium ion adsorption effects mainly include ion sieve adsorbents, aluminum adsorbents and natural mineral adsorbents. Among these three types of adsorbent materials, the aluminum adsorbents are currently mainly used in industrial applications. Aluminum adsorbents are essentially lithium-aluminum composite hydroxides that have selective adsorption effects on lithium ions. At present, aluminum adsorbents are mostly synthesized by chemical precipitation. On the one hand, the synthesis cost is relatively high. On the other hand, due to the properties of the aluminum adsorbent materials themselves, the amount of lithium ions adsorbed is small. At present, in order to further improve the adsorption capacity of aluminum adsorbent materials for lithium ions, the main method is to increase the specific surface area of the material and improve the interlayer anions, but the effect is limited.
[0004] Therefore, it is very necessary to develop a low-cost lithium ion adsorbent that can effectively separate lithium ions from brine. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a montmorillonite-based composite lithium ion adsorbent and a preparation method thereof. The method uses natural montmorillonite as a raw material to prepare a montmorillonite-based organic-inorganic composite lithium ion adsorbent.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a composite lithium ion adsorbent based on montmorillonite, the preparation method comprising the following steps:
[0007] (1) dissolving a surfactant in deionized water and adjusting the pH to 8-10, adding montmorillonite raw material powder and stirring at room temperature, adding ethyl orthosilicate for ultrasonic dispersion, continuing to stir, filtering, washing and drying the mixture, solid-phase calcining to obtain composite montmorillonite powder, and cooling to room temperature for use;
[0008] (2) adding the composite montmorillonite powder and silane coupling agent in step (1) into toluene, filtering after the reaction, and drying the solid phase to obtain the powder of step (2) for standby use;
[0009] (3) After mixing the powder of step (2) with chloroacetic acid solution, adding NaOH solution to adjust the pH to 8-8.5, reacting at room temperature, filtering, and drying the solid phase to constant weight to obtain the powder of step (3);
[0010] (4) dissolving taurine and NaOH in ethanol, mixing evenly with the powder of step (3), refluxing the mixture, filtering and washing the mixture until it is neutral, and drying the solid phase to a constant weight to obtain the powder of step (4);
[0011] (5) Dissolve LiCl and AlCl3 in deionized water, add the powder from step (4), adjust the pH to 4-5 with NaOH solution, continue stirring the reaction at room temperature, and obtain a montmorillonite-based composite lithium ion adsorbent after filtering and drying.
[0012] The purpose and mechanism of each step in the preparation method of the present application are as follows: In step (1), the surfactant reacts with montmorillonite, enters the interlayer of montmorillonite and is loaded on its surface, providing active sites for the subsequent introduction of SiO2; the purpose of adding ethyl orthosilicate for ultrasonic dispersion and calcination is to allow active SiO2 to enter the interlayer of montmorillonite, exfoliate the montmorillonite, increase its specific surface area, and load the active SiO2 on the exfoliated montmorillonite to give it more active sites. Step (2) is to react the hydroxyl groups on the surface of active SiO2 with a silane coupling agent to introduce amino groups (-NH2). Step (3) is to dehydrogenate the amino groups (-NH2) on the surface of SiO2 and dechlorinate them with chloroacetic acid, thereby introducing carboxyl groups (-COOH), thereby introducing carboxyl groups in SiO2, i.e. -NH-COOH. Step (4) is to react the amino groups (-NH2) in the taurine structure with the carboxyl groups (-COOH) in SiO2, and introduce sulfonic acid groups, -NH-CO-NH-(CH2)2-SO3H. Step (5) is to load LiCl·2Al(OH)3·nH2O on the surface of montmorillonite and active SiO2 by co-precipitation, thereby obtaining a montmorillonite-based organic-inorganic composite lithium ion adsorbent having sulfonic acid groups and LiCl·2Al(OH)3·nH2O.
[0013] As a preferred embodiment of the preparation method of the present invention, in the step (1), the montmorillonite raw material powder is obtained by crushing, and the mesh size is less than 200 mesh; the surfactant is at least one of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, octadecyl dihydroxyethyl betaine, and dodecyl dihydroxyethyl betaine.
[0014] As a preferred embodiment of the preparation method of the present invention, in the step (1), the mass volume ratio of montmorillonite raw material powder to deionized water is 100 g:250 mL, the mass volume ratio of montmorillonite raw material powder to tetraethyl orthosilicate is 100 g:(10-20) mL, and the mass ratio of montmorillonite raw material powder to surfactant is 100:(0.2-0.5).
[0015] As a preferred embodiment of the preparation method of the present invention, in the step (1), the stirring time at room temperature is 3 to 6 hours, the ultrasonic dispersion time is 0.5 to 1 hour, the stirring time is continued for 6 to 12 hours, and the calcination is to place the solid phase in a muffle furnace and calcine at 500 to 600° C. for 1 to 3 hours.
[0016] As a preferred embodiment of the preparation method of the present invention, in the step (2), the silane coupling agent is at least one of KH791, KH792, and KH550, the mass volume ratio of the montmorillonite raw material powder to toluene is 100 g:250 mL, and the mass volume ratio of the montmorillonite raw material powder to the silane coupling agent is 100 g:(5-10) mL.
[0017] As a preferred embodiment of the preparation method of the present invention, in step (2), the reaction temperature is 110-140°C, the reaction time is 18-30h, and the drying condition is 110-140 o C for 24h.
[0018] As a preferred embodiment of the preparation method of the present invention, in the step (3), the concentration of the chloroacetic acid solution is 1.0-2.0 g / L, the mass volume ratio of the montmorillonite raw material powder to the chloroacetic acid solution is 100 g: 250 mL, the reaction time is 12-36 h, and the drying temperature is 80 o C.
[0019] As a preferred embodiment of the preparation method of the present invention, in step (4), the mass ratio of montmorillonite raw material powder to taurine is 100: (2-5), the mass ratio of the powder in step (3) to NaOH is 100: (0.5-2.0), the mass volume ratio of montmorillonite raw material to ethanol is 100 g: 250 mL, the reaction temperature is 110-150 ° C, the reaction time is 12-36 h, and the drying temperature is 80 o C.
[0020] As a preferred embodiment of the preparation method of the present invention, in step (5), the mass ratio of montmorillonite raw material powder to LiCl is 100: (5-15), the mass ratio of montmorillonite raw material powder to AlCl3 is 100: (30-50), the mass volume ratio of the powder in step (4) to deionized water is 100g: 250mL, the concentration of NaOH solution is 1mol / L, the reaction time is 3-6h, and the drying temperature is 80 o C.
[0021] In a second aspect, the present invention provides a montmorillonite-based composite lithium ion adsorbent prepared by the above-mentioned preparation method.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present application uses cheap and readily available natural montmorillonite as a raw material, and introduces LiCl·2Al(OH)3·nH2O and sulfonic acid groups into montmorillonite by SiO2 activation, chemical grafting and co-precipitation, thereby preparing a montmorillonite-based organic-inorganic composite lithium ion adsorbent. Compared with the conventional inorganic lithium aluminum composite hydroxide synthesized using AlCl3, NaOH and LiCl chemical reagents, the amount of AlCl3, NaOH and LiCl is significantly reduced, and the introduction of new lithium ion adsorption sites (sulfonic acid groups) is not only beneficial to the extraction of lithium resources from brine, but also beneficial to the effective utilization of montmorillonite resources.
[0024] (2) The natural montmorillonite raw material used in this application is easy to obtain and has low cost.
[0025] (3) The organic-inorganic composite lithium ion adsorbent based on montmorillonite prepared by the preparation method of the present application can effectively separate lithium ions from brine. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a flow chart of the preparation process of the montmorillonite-based composite lithium ion adsorbent of the present application.
[0027] Figure 2 These are SEM images of the montmorillonite raw material of the present application, the exfoliated SiO2 activated montmorillonite prepared in Example 3, and the adsorbent prepared in Example 3, wherein (a) is the SEM image of the montmorillonite raw material, (b) is the SEM image of the exfoliated SiO2 activated montmorillonite prepared in Example 3, and (c) and (d) are SEM images of the montmorillonite-based composite lithium ion adsorbent prepared in Example 3.
[0028] Figure 3 XRD diagram of the montmorillonite raw material of the present application and the montmorillonite-based composite lithium ion adsorbent prepared in Example 3. DETAILED DESCRIPTION
[0029] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0030] The preparation process flow chart of the composite lithium ion adsorbent based on montmorillonite in this application is as follows Figure 1 shown.
[0031] The method for testing the lithium ion adsorption and regeneration performance in this application is as follows:
[0032] (1) Add 1.0 g of adsorbent into a conical flask containing 25 mL of brine and adsorb for 6 to 12 h at room temperature. Determine the lithium ion concentration in the brine by ICP-OES and calculate the amount of lithium ions adsorbed by the adsorbent.
[0033] (2) The adsorbent after adsorbing lithium ions in step (1) was shaken and desorbed with 50 mL of dilute HCl solution with a pH of 4 at room temperature for 6 h, and then the adsorbent was dried for later use.
[0034] (3) The steps (1) and (2) were repeated five times to test the recycling performance of the adsorbent. The lithium ion concentration of the brine used in the adsorption process was 67.42 mg / L. Example 1
[0035] A method for preparing a composite lithium ion adsorbent based on montmorillonite, comprising the following steps:
[0036] (1) After natural montmorillonite is crushed, powders below 200 mesh are collected for later use. 250 mL of 0.2 g octadecyl dihydroxyethyl betaine solution is adjusted to pH 8, 100.0 g montmorillonite powder is added and stirred at room temperature for 4 h. Then 10 mL of ethyl orthosilicate is added and ultrasonically dispersed for 0.5 h. Stirring is continued for 6 h. The mixture is filtered, washed and dried. The solid phase is placed in a muffle furnace and calcined at 550 ° C for 2 h, and then cooled to room temperature for later use.
[0037] (2) The montmorillonite powder calcined in step (1) was reacted with 5 mL of silane coupling agent KH550 and 250 mL of toluene at 120°C for 30 h and then filtered. o C and then dried for 24 hours.
[0038] (3) The powder obtained in step (2) was mixed with 250 mL of 1.0 g / L chloroacetic acid solution, and NaOH solution was added to adjust the pH to 8.2. After reacting at room temperature for 24 h, the mixture was filtered and the solid phase was stirred at 80 o C is dried to constant weight.
[0039] (4) 2.5 g of taurine and 0.8 g of NaOH were dissolved in 250 mL of ethanol, mixed evenly with the powder obtained in step (3), and refluxed at 110 °C for 24 h. The mixture was filtered and washed to neutrality, and the solid phase was heated at 80 °C. o C is dried to constant weight for later use.
[0040] (5) Dissolve 8 g LiCl and 35 g AlCl3 in 250 mL deionized water, add the solid phase obtained in step (4), adjust the pH to 4 with 1 mol / L NaOH solution, and continue stirring the reaction at room temperature for 3 h. o The solid phase after drying is an organic-inorganic composite lithium ion adsorbent based on montmorillonite.
[0041] Lithium ion adsorption and regeneration performance in this example: 1.0 g of the adsorbent was weighed and mixed with 25 mL of brine in a conical flask, and adsorbed at room temperature for 6 hours. After testing, the lithium ion adsorption amount was 3.15 mg / g. After 5 cycles of adsorption-desorption, the adsorbent adsorbed 2.62 mg / g of lithium ions.
[0042] Example 2
[0043] A method for preparing a composite lithium ion adsorbent based on montmorillonite, comprising the following steps:
[0044] (1) After natural montmorillonite is crushed, powders below 200 mesh are collected for later use. 250 mL of 0.3 g dodecyltrimethylammonium bromide solution is adjusted to pH 9, 100.0 g montmorillonite powder is added, and the mixture is stirred at room temperature for 5 h. Then 15 mL of ethyl orthosilicate is added, ultrasonically dispersed for 1 h, and stirred for 10 h. The mixture is filtered, washed, and dried. The solid phase is calcined at 600 ° C in a muffle furnace for 1 h, and then cooled to room temperature for later use.
[0045] (2) The montmorillonite powder calcined in step (1) was reacted with 8 mL of silane coupling agent KH792 and 250 mL of toluene at 110°C for 20 h and then filtered. o C and then dried for 24 hours.
[0046] (3) The powder obtained in step (2) was mixed with 250 mL of 1.6 g / L chloroacetic acid solution, and NaOH solution was added to adjust the pH to 8.5. The mixture was reacted at room temperature for 18 h and then filtered. The solid phase was stirred at 80 o C is dried to constant weight.
[0047] (4) 4.0 g of taurine and 1.6 g of NaOH were dissolved in 250 mL of ethanol, mixed evenly with the powder obtained in step (3), and refluxed at 130 °C for 36 h. The mixture was filtered and washed to neutrality, and the solid phase was heated at 80 °C. oC is dried to constant weight for later use.
[0048] (5) Dissolve 10 g LiCl and 40 g AlCl3 in 250 mL deionized water, add the solid phase obtained in step (4), adjust the pH to 5 with 1 mol / L NaOH solution, and continue stirring the reaction at room temperature for 6 h. o The solid phase after drying is an organic-inorganic composite lithium ion adsorbent based on montmorillonite.
[0049] Lithium ion adsorption and regeneration performance in this example: 1.0 g of the adsorbent was weighed and mixed with 25 mL of brine in a conical flask, and adsorbed at room temperature for 6 hours. After testing, the lithium ion adsorption amount was 3.65 mg / g. After 5 cycles of adsorption-desorption, the adsorbent adsorbed 3.06 mg / g of lithium ions.
[0050] Example 3
[0051] A method for preparing a composite lithium ion adsorbent based on montmorillonite, comprising the following steps:
[0052] (1) After natural montmorillonite is crushed, the powder below 200 mesh is collected for use, 250mL of 0.4g hexadecyltrimethylammonium bromide solution is adjusted to pH 9.5, 100.0g of montmorillonite powder is added and stirred at room temperature for 6h, 20mL of ethyl orthosilicate is added, ultrasonically dispersed for 1h, and stirred for 10h. After the mixture is filtered, washed and dried, the solid phase is placed in a muffle furnace and calcined at 500℃ for 3h to obtain composite montmorillonite powder, which is cooled to room temperature for use.
[0053] (2) The montmorillonite powder calcined in step (1) was reacted with 10 mL of silane coupling agent KH791 and 250 mL of toluene at 130°C for 24 h and then filtered. o C and then dried for 24 hours.
[0054] (3) The powder obtained in step (2) was mixed with 250 mL of 2.0 g / L chloroacetic acid solution, and NaOH solution was added to adjust the pH to 8.5. After reacting at room temperature for 12 h, the mixture was filtered and the solid phase was stirred at 80 °C. o C is dried to constant weight.
[0055] (4) 5.0 g of taurine and 2.0 g of NaOH were dissolved in 250 mL of ethanol, mixed evenly with the powder obtained in step (3), and refluxed at 150 °C for 12 h. The mixture was filtered and washed to neutrality, and the solid phase was heated at 80 °C. o C is dried to constant weight for later use.
[0056] (5) Dissolve 15 g LiCl and 50 g AlCl3 in 250 mL deionized water, add the solid phase obtained in step (4), adjust the pH to 4 with 1 mol / L NaOH solution, continue stirring the reaction at room temperature for 6 h, filter, and 80 o The solid phase after drying is an organic-inorganic composite lithium ion adsorbent based on montmorillonite.
[0057] Lithium ion adsorption and regeneration performance of this example: 1.0 g of adsorbent was weighed and mixed with 25 mL of brine in a conical flask, and adsorbed at room temperature for 6 hours. After testing, the lithium ion adsorption amount was 4.26 mg / g. After 5 cycles of adsorption-desorption, the adsorbent adsorbed 3.68 mg / g of lithium ions.
[0058] The SEM images of the montmorillonite raw material of the present application, the exfoliated SiO2 activated montmorillonite prepared in Example 3, and the adsorbent prepared in Example 3 are as follows: Figure 2 As shown, (a) is the SEM image of the montmorillonite raw material, which shows that the montmorillonite raw material is in granular form as a whole and has lamellar structural characteristics, (b) is the SEM image of the exfoliated SiO2 activated montmorillonite prepared in Example 3, which shows that the montmorillonite particles are broken and the lamellar layers are exfoliated, and a large number of nanoparticles are loaded on the lamellar layers, and the nanoparticles are SiO2, (c) and (d) are SEM images of different multiples of the montmorillonite-based composite lithium ion adsorbent prepared in Example 3, which shows that after exfoliation, SiO2 loading, grafting and loading LiCl·2Al(OH)3·nH2O, dense nanoparticles are attached to the surface of the montmorillonite. The XRD pattern of the montmorillonite-based composite lithium ion adsorbent prepared in this example is shown in FIG. Figure 3 As shown, it can be seen that the prepared adsorbent not only has the structural characteristics of montmorillonite, but also has the characteristic peaks of LiCl·2Al(OH)3·nH2O.
[0059] Example 4
[0060] A method for preparing a composite lithium ion adsorbent based on montmorillonite, comprising the following steps:
[0061] (1) After natural montmorillonite is crushed, powders below 200 mesh are collected for later use. 250 mL of 0.5 g dodecyl dihydroxyethyl betaine solution is adjusted to pH 9.0, 100.0 g of montmorillonite powder is added, and the mixture is stirred at room temperature for 3 h. Then 18 mL of ethyl orthosilicate is added, ultrasonically dispersed for 1 h, and stirred for 12 h. The mixture is filtered, washed, and dried. The solid phase is placed in a muffle furnace and calcined at 550 ° C for 3 h, and then cooled to room temperature for later use.
[0062] (2) The montmorillonite powder calcined in step (1) was reacted with 6 mL of silane coupling agent KH791 and 250 mL of toluene at 140°C for 18 h and then filtered.o C and then dried for 24 hours.
[0063] (3) The powder obtained in step (2) was mixed with 250 mL of 2.0 g / L chloroacetic acid solution, and NaOH solution was added to adjust the pH to 8.5. The mixture was reacted at room temperature for 36 h and then filtered. The solid phase was stirred at 80 o C is dried to constant weight.
[0064] (4) 3.0 g of taurine and 1.4 g of NaOH were dissolved in 250 mL of ethanol, mixed evenly with the powder obtained in step (3), and refluxed at 120 °C for 20 h. The mixture was filtered and washed to neutrality, and the solid phase was heated at 80 °C. o C is dried to constant weight for later use.
[0065] (5) Dissolve 5 g LiCl and 30 g AlCl3 in 250 mL deionized water, add the solid phase obtained in step (4), adjust the pH to 4 with 1 mol / L NaOH solution, and continue stirring the reaction at room temperature for 5 h. o The solid phase after drying is an organic-inorganic composite lithium ion adsorbent based on montmorillonite.
[0066] Lithium ion adsorption and regeneration performance of this example: 1.0 g of adsorbent was weighed and mixed with 25 mL of brine in a conical flask, and adsorbed at room temperature for 6 hours. After testing, the lithium ion adsorption amount was 2.76 mg / g. After 5 cycles of adsorption-desorption, the adsorbent adsorbed 2.48 mg / g of lithium ions.
[0067] Comparative Example 1
[0068] The specific method is the same as that of Example 3, except that the chemical grafting process in steps (2) to (4) is not performed, and the other conditions remain unchanged. The prepared adsorbent is used to adsorb lithium ions in brine. The adsorbent prepared in this way has an adsorption capacity of 1.98 mg / g for lithium ions.
[0069] Comparative Example 2
[0070] The specific method is the same as that of Example 3, except that in step (1), no tetraethyl orthosilicate is added for reaction, that is, no active SiO2 loading is performed. The other conditions remain unchanged, and the prepared adsorbent is used for adsorption of lithium ions in brine. The adsorbent prepared in this way has an adsorption capacity of 1.84 mg / g for lithium ions.
[0071] Comparative Example 3
[0072] The specific method is the same as that of Example 3, except that the aluminum-lithium co-precipitation reaction in step (5) is not carried out, and the other steps remain unchanged. The prepared adsorbent is used for adsorption of lithium ions in brine. The adsorbent prepared in this way has an adsorption capacity of 1.42 mg / g for lithium ions.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite lithium ion adsorbent based on montmorillonite, characterized in that: The preparation method comprises the following steps: (1) dissolving a surfactant in deionized water and adjusting the pH to 8-10, adding montmorillonite raw material powder and stirring at room temperature, adding ethyl orthosilicate for ultrasonic dispersion, continuing to stir, filtering, washing and drying the mixture, solid-phase calcining to obtain composite montmorillonite powder, and cooling to room temperature for use; (2) adding the composite montmorillonite powder and silane coupling agent in step (1) into toluene, filtering after the reaction, and drying the solid phase to obtain the powder of step (2) for standby use; (3) After mixing the powder of step (2) with chloroacetic acid solution, adding NaOH solution to adjust the pH to 8-8.5, reacting at room temperature, filtering, and drying the solid phase to constant weight to obtain the powder of step (3); (4) dissolving taurine and NaOH in ethanol, mixing evenly with the powder of step (3), refluxing the mixture, filtering and washing the mixture until it is neutral, and drying the solid phase to a constant weight to obtain the powder of step (4); (5) Dissolve LiCl and AlCl3 in deionized water, add the powder from step (4), adjust the pH to 4-5 with NaOH solution, continue stirring the reaction at room temperature, and obtain a montmorillonite-based composite lithium ion adsorbent after filtering and drying; In the step (1), the mass volume ratio of montmorillonite raw material powder to ethyl orthosilicate is 100 g: (10-20) mL; In the step (1), the surfactant is at least one of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, octadecyl dihydroxyethyl betaine, and dodecyl dihydroxyethyl betaine; In the step (2), the silane coupling agent is at least one of KH791, KH792, and KH550.
2. The preparation method according to claim 1, characterized in that In the step (1), the montmorillonite raw material powder is crushed to obtain a powder with a mesh size of less than 200 meshes.
3. The preparation method according to claim 1, characterized in that: In the step (1), the mass volume ratio of the montmorillonite raw material powder to deionized water is 100 g:250 mL, and the mass ratio of the montmorillonite raw material powder to the surfactant is 100:(0.2-0.5).
4. The preparation method according to claim 1, characterized in that: In the step (1), the stirring time at room temperature is 3 to 6 hours, the ultrasonic dispersion time is 0.5 to 1 hour, the stirring time is continued for 6 to 12 hours, and the calcination is to place the solid phase in a muffle furnace and calcine at 500 to 600° C. for 1 to 3 hours.
5. The preparation method according to claim 1, characterized in that: In the step (2), the mass volume ratio of the montmorillonite raw material powder to toluene is 100 g:250 mL, and the mass volume ratio of the montmorillonite raw material powder to the silane coupling agent is 100 g:(5-10) mL.
6. The preparation method according to claim 1, characterized in that: In the step (2), the reaction temperature is 110-140°C, the reaction time is 18-30h, and the drying condition is 110-140 o C for 24h.
7. The preparation method according to claim 1, characterized in that: In the step (3), the concentration of the chloroacetic acid solution is 1.0-2.0 g / L, the mass volume ratio of the montmorillonite raw material powder to the chloroacetic acid solution is 100 g:250 mL, the reaction time is 12-36 h, and the drying temperature is 80 o C.
8. The preparation method according to claim 1, characterized in that: In the step (4), the mass ratio of montmorillonite raw material powder to taurine is 100:(2-5), the mass ratio of montmorillonite raw material powder to NaOH is 100:(0.5-2.0), the mass volume ratio of montmorillonite raw material powder to ethanol is 100 g:250 mL, the reaction temperature is 110-150° C., the reaction time is 12-36 h, and the drying temperature is 80 o C.
9. The preparation method according to claim 1, characterized in that: In the step (5), the mass ratio of montmorillonite raw material powder to LiCl is 100:(5-15), the mass ratio of montmorillonite raw material powder to AlCl3 is 100:(30-50), the mass volume ratio of montmorillonite raw material powder to deionized water is 100 g:250 mL, the concentration of NaOH solution is 1 mol / L, the reaction time is 3-6 h, and the drying temperature is 80 o C.
10. A composite lithium ion adsorbent based on montmorillonite prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of material capable of adsorbing lithium
CN108421539A
Preparation method of bauxite-based aluminum lithium ion adsorbent and method for extracting lithium from brine
CN117358196A